ANALISIS KEPUTUSAN PEMBELIAN HANDPHONE VIVO (Studi Kasus Konsumen Gadget Mart Pelaihari) - Siti Raesa Rizki P; Akhmad Samhudi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
This research is based on a theoretical framework, expert ideas, or the understanding of researchers based on their experience, then developed into problems and solutions that are proposed to obtain justification (Verification) in the form of emperical data support in the field. This study aims to find out and analyze how much influence the variables of product quality, price and promotion on purchasing decisions on VIVO mobile phones. The method used in this study is a quantitative method, with a population of 40, a sample of 40 people and data analysis techniques with research instruments validity test, reliability test and using multiple linear regression. The results of this study indicate that the Product Quality, Price and Promotion variables individually and together influence the VIVO Mobile Purchase Decision on the Pelaihari Mart Gadget. Meanwhile, based on the results of the F Test at the level of α of 5%, it proves that all the independent variables have a significant effect on the dependent variables together (simultaneous). Adjusted determination (R2) is 0.505 or 50.5%, this shows the amount of contribution given by all independent variables on the dependent variable.